Digital inequities and emotional resilience: understanding the impact of the COVID-19 pandemic on preclinical medical students - William A. H. Schwartz; Tazim S. Merchant; Isi Sturla; Leah C. Neubauer (Frontiers in Medicine)
IntroductionThe COVID-19 pandemic profoundly disrupted medical education, posing unique challenges for first-year medical students transitioning into preclinical training. Traditional in-person instruction was replaced with virtual and hybrid learning, creating barriers related to digital access, social isolation, academic engagement, and mental health. This study explores the academic, social, and emotional impacts of these disruptions to identify actionable strategies for fostering resilience and inclusivity in medical education systems.MethodsA pragmatic research framework guided a student-led needs assessment via a survey distributed to first-year medical students during the 2020–2021 academic year. The survey included demographic questions and open-ended prompts about academic, social, and emotional experiences. Data from 57 respondents (36% response rate) were analyzed thematically using the constant comparative method, and findings were validated through member-checking.ResultsFive key themes emerged: isolation, difficulty engaging with virtual curricula, lack of community, mental health challenges, and perceived convenience of virtual learning. Isolation was the most prominent theme, with students reporting emotional distress and limited peer connections. Engagement difficulties stemmed from screen fatigue, reduced accountability, and blurred personal-academic boundaries. Mental health concerns, including anxiety and emotional exhaustion, were widespread, although some students cited protective coping strategies such as structured routines. A small subset highlighted benefits of virtual learning flexibility.DiscussionThese findings underscore the need for hybrid curricular models that balance digital flexibility with structured opportunities for peer interaction, enhanced mental health services, and sustained institutional support. Addressing these challenges is critical for building equitable and resilient medical education systems prepared for future crises.